The interplay between gut bacteria and targeted therapies: implications for future cancer treatments - Juan He; Yu Chen; Huakan Zhao; Yongsheng Li (Molecular Medicine)
Abstract Targeted therapy represents a form of cancer treatment that specifically focuses on molecular markers regulating the growth, division, and dissemination of cancer cells. It serves as the cornerstone of precision medicine and is associated with fewer adverse effects compared to conventional chemotherapy, thus enhancing the quality of patient survival. These make targeted therapy as a vital component of contemporary anti-cancer strategies. Although targeted therapy has achieved excellent anti-cancer results, there are still many factors affecting its efficacy. Among the numerous factors affecting anti-cancer treatment, the role of intestinal bacteria and its metabolites are becoming increasingly prominent, particularly in immunotherapy. However, their effects on anticancer targeted therapy have not been systematically reviewed. Herein, we discuss the crosstalk between gut bacteria and anticancer targeted therapies, while also highlighting potential therapeutic strategies and future research directions.